2004
DOI: 10.1111/j.1751-3928.2004.tb00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Simulation Model for the Formation of Methane Hydrate to the Nankai Trough and the Blake Ridge: Natural Examples of Two End‐member Cases

Abstract: Abstract:Simulation experiments with a one-dimensional static model for formation of methane hydrate are used to demonstrate models of hydrate occurrence and its generation mechanism for two end-member cases. The simulation results compare well with experimental data for two natural examples (the Nankai Trough and the Blake Ridge).At the MITI Nankai Trough wells, the hydrate occurrence is characterized by strongly hydrated sediments developing just above the BGHS. Such occurrence can be reproduced well by simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The hydrate accumulation at site 997 has previously been modeled by Xu and Ruppel [1999], Davie and Buffett [2001, 2003a, 2003b], Nimblett and Ruppel [2003], and Baba and Katoh [2004]. Xu and Ruppel [1999] used a steady state analytical model to estimate the upward methane flux required for the base of the hydrate occurrence zone to coincide with the bottom of the hydrate stability zone and the top of the free gas zone.…”
Section: Model Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrate accumulation at site 997 has previously been modeled by Xu and Ruppel [1999], Davie and Buffett [2001, 2003a, 2003b], Nimblett and Ruppel [2003], and Baba and Katoh [2004]. Xu and Ruppel [1999] used a steady state analytical model to estimate the upward methane flux required for the base of the hydrate occurrence zone to coincide with the bottom of the hydrate stability zone and the top of the free gas zone.…”
Section: Model Applicationsmentioning
confidence: 99%
“…To model the inferred hydrate volume, Davie and Buffett [2001] had to assume a rather high value (1.1%) for the available organic carbon at the seafloor. Baba and Katoh [2004], using a one‐dimensional static model, found that the hydrate saturation at site 997 could be reproduced using an available organic carbon content of 0.78%. Hydrate accumulation due to migration of methane‐bearing fluids from a deeper source was investigated by Davie and Buffett [2003a, 2003b].…”
Section: Model Applicationsmentioning
confidence: 99%
“…A similar interpretation is given by mathematical simulation using 1-dimensional static model to simulate accumulation process of marine gas hydrate. In this simulation, strongly hydrated sediments can be calculated just above the free gas zone by setting upward migration of gas-bearing fluid below the BGHS (Baba and Katoh, 2004).…”
Section: Distribution and Origin Of Bsrmentioning
confidence: 99%
“…Reactive gas hydrate formation and accumulation in marine sediments was initially simulated using simple 1‐D models [e.g., Baba and Katoh , ; Davie and Buffett , ; Garg et al ., ; Katoh et al ., ; Rempel and Buffett , ]. Subsequently, these models were augmented to include the Anaerobic Oxidation of Methane (AOM) [e.g., Burwicz et al ., ; Chatterjee et al ., ; Egeberg and Dickens , ; Torres et al ., ; Wallmann et al ., ], the permeability evolution due to gas hydrates formation [ Nimblett and Ruppel , ; Seol and Kneafsey , ], and the influence of a free‐gas layer underlying gas hydrate deposits [ Bhatnagar et al ., ].…”
Section: Introductionmentioning
confidence: 99%